The Effect of Simple Triage and Rapid Treatment (START) Training on Cognitive, Affective, and Psychomotor Skills in Performing START Triage Among Medical Staff and Healthcare Professionals - Faizatiwahida, Novia; Alfrisa, Bagus; Nurjannah, Intansari; Alim, Syahirul (Universitas Muhammadiyah Surakarta, 2025)
The increasing incidence of disasters globally underscores the importance of preparedness to minimize errors during disaster triage. Inadequate triage can elevate mortality and disability rates. The commonly used and easily applicable triage system is known as the START method. Currently, there is no effective training available for medical and healthcare professionals to enhance cognitive, affective, and psychomotor skills in the context of disaster triage. This study aims to understand the significance of Simple Triage and Rapid Treatment (START) training on cognitive, affective, and psychomotor skills in performing START triage among Medical and Healthcare Professionals at Cangkringan, Pakem, and Turi Health Centers. The research design employed in this study is a quasi-experiment utilizing a pre- and post-test without a control group design. The respondents for this study are medical and healthcare professionals at Puskesmas Cangkringan, Pakem, and Turi, totaling 43 individuals. The intervention applied involves providing START triage training conducted over one day. Both pre-test and post-test assessments are carried out on the same day, with the post-test immediately following the completion of the training. While this approach may not fully capture long-term knowledge, attitude, and skill improvements, it is useful for assessing the direct impact of the training. Data collection involves the use of cognitive and affective questionnaires, along with a psychomotor observation sheet. The data analysis is conducted using a paired t-test. There is an increase in the average scores for cognitive (57.21 vs. 78.60), affective (33.56 vs. 36.35), and psychomotor (18.98 vs. 23.02) aspects before and after the training. The training in Simple Triage and Rapid Treatment has a significant influence on the cognitive (p < 0.001), affective (p < 0.001), and psychomotor (p < 0.001) skills of medical and healthcare professionals in performing START triage. The START training is crucial and should be conducted in every community health center (puskesmas) to enhance the competence of medical and healthcare professionals in performing START triage.